A place of home: An interactive audio installation - Jogan, M.; Batinic, M.; Fucak, I.; Modic, J.; Pipan, D.; Raceta, M. (2009 International Symposium ELMAR, 2009)
A place of home is an interactive audio installation composed of six audio clips that refer to the artist's deliberation on the subject of home. The visitor enters a completely dark and empty space as an active explorer: at the same time, he is both a visitor and a part of the work. An auditive narration describes the artist's home and her sense of home, where the focus is on the perception of sound and space. The sound is activated and controlled by the patterns of motion that the user generates during exploration. Since the gallery is in a complete darkness, the space is observed by a vision system that senses wavelengths above the visible spectra. From the human point of view, there is no visual information in darkness. There are no signs or symbols to form associations; in darkness, the visitor is ¿invisible¿ and therefore free to explore the work.